A study on stressors of academic stress among students pursuing entrepreneurship professional courses - MS. B. NEERAJA; MS. JANANI. E (The journal of contemporary issues in business and government, 2020)
Stress can exist when working at a fast place, doing difficult problems, or listening to someone shout at you. It can be brought about through conflicts, making decisions, or otherwise straining abilities, or it can exist because of numerous social demands on time. We have noted that emotional states tend not to be long lasting, whether they are unpleasant emotions like fear, or pleasant ones, such as joy. Yet on occasion such states may persist for long periods of time, or they may reach excessively high levels. When this happens, the result typically is labeled "stress", and its manifestation in psychological as well as physiological terms. The sample was selected by using a simple random sampling technique. The present study reveals that the higher secondary students are having moderate level of academic stress and irrespective of sub samples of the higher secondary students are having moderate level of academic stress. The male student’s academic stress is higher than female students. The urban student’s academic stress is higher than rural student. The students whose parent’s education as literacy level academic stress is higher than their counterpart.